A case of a colo-colic intussusception secondary to adenocarcinoma of the sigmoid colon - Bhalerao, Aishwarya; Kumar, Supreet; Shah, Suryalok Pratap; Pandey, Alok Kumar; Tandon, Vivek; Govil, Deepak (International Surgery Journal, 2024)
When a more proximal section of the bowel (intussusceptum) invaginates into the more distal bowel (intussuscipiens), it results in intussusception. Changes in intestinal peristalsis at the intraluminal lesion, which serves as a lead point for the intussusceptum, is assumed to be the mechanism. Adult cases of intestinal intussusception are uncommon; they make up about 1% of all bowel obstructions. We describe a case of a colo-colic intussusception caused by an adenocarcinoma of the sigmoid colon. The most frequent urgent condition in children is intussusception, although it is extremely uncommon in adults. It is challenging to make the diagnosis based only on the history and physical exam results. Since a malignant pathology typically serves as a lead point in adulthood, as opposed to childhood, treatment of this pathology still raises questions. Accurately identifying and comprehending relevant symptoms, signs, and imaging results is crucial for an adult intussusception’s early diagnosis and proper treatment. It’s not always obvious how to treat adult intussusception appropriately. Regarding the reduction prior to resection in sigmoido rectal intussusception cases, there is disagreement. A useful diagnostic marker of colorectal intussusception in bowel-within-bowel configuration cases is the target-like sign on CT images, which shows the bowel’s layers duplicated to form concentric rings. Quick and precise diagnosis will be facilitated by a high index of suspicion combined with radiological investigation. A high degree of suspicion of a malignant etiology is important in cases of adult intussusception.